Application of a novel high resolution widefield surface plasmon microscope in cell engineering, wound healing and development of new binding assays - Abdul Jamil, Muhammad Mahadi (2007)
Surface Plasmon (SP) microscope systems are mostly built around the prism based Krctschmann configuration. In thcsc systcms the generation of Surface Plasmons (SPs) is achieved by p-polarized light striking a metallised prism surfacc at a spccific angle and then monitoring thc intensity of the reOected light. Thus in these systems. an image of the material can be obtained in terms of an intensity map. in which the intcnsity of thc image is dcpendent on the way the light couples into the SPs. The drawback of these systems is that lateral resolution relies on the ability of plasmons to propagate along the metallised layer. The lateral resolution is thus limited to a few microns. Therefore, a new microscope systcm was developed. i.e. thc Widcficld Surface Plasmon Resonance (WSPR) microscope. that is not only capable of analysing molecular interactions at high vertical resolutions. but also enables SP imaging at much higher lateral resolution than prism based systcms. The functionality of thc novel (WSPR) microscope has been investigated by imaging a scquence of binding events between micropattcrncd cxtracellular matrix proteins and their specific antibodies both in air and real-time. Using the WSPR systcm a changc in contrast was observed with each protein binding cvcnts. Images produced via the WSPR system were analyzcd and comparcd qualitatively and quantitatively. The preliminary results acquired for these binding studics between antibody/antigens dcmonstrate that the WSPR systcm capablc of resolving features down to 260nm although the theoretically proven lateral resolution of the WSPR system is -500nm. Cell surface interactions undcr two diffcrent culture conditions. i.e. HaCaTs cultured on SPR substrate with Transforming Growth Factor ~3 (TGF~3) (50ng/lII/) and without TGF~3 were also invcstigated. It was found that I-IaCaTs cultured in the presence of TGF~3 showed enhanced division and motility along with decreased cell attachmcnt as compared with cclls maintained in TGF~3 free media. It is believed that cellular signalling by TGF~3 is very important for enhancing tissue development in wound rcpair. It is confirmed that the WSPR microscope described here can be used to study sequential monomolecular layer of antibody/antigen interactions binding cvents and examination of cell surface intcrfacial intcractions at latcral scales of less than one micron without the need for traditional immunoOuorescent labelling. These rcsults have significant implications in the developmcnt of ncw brecd fast binding assays system and in enabling high resolution detailed examination of the cell surface couplings and ccll signalling proccsses involvcd in cell attachmcnt and migration.